Pengaruh Standarisasi Produk dan Sertifikasi Halal dalam Meningkatkan Volume Penjualan: Studi Kasus UMKM Krecek Kulit Ashif Jatirejo - Salsa Chabita Saraswati; Khoirotun Nadhiroh; Nadia Ananda Putri Ikhtiarni; Faizal Adi Mukti; Ika Wahyu Arlina; Muhammad Syifaul Anwar; Nur Laila Handayani; Hardi Utomo (Lembaga Pengembangan Kinerja Dosen, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the economy and community independence. However, the great potential of home-based businesses is often hindered by administrative issues related to business legality. This research focuses on UMKM Krecek Kulit Sapi Ashif in Jatirejo Village, which has been operating since 2018 but lacks a Business Identification Number (NIB), Household Industry Food (PIRT) permit, and halal certification due to perceived complex procedures. The main objective of this activity is to strengthen business management through product standardization and obtaining legal certifications to enhance the competitiveness of this MSME. The research method used a descriptive qualitative approach with a community service method based on mentoring, including observation, in-depth interviews, and hands-on practice in managing documents through the Online Single Submission system. The results show that through phased mentoring, UMKM Krecek Kulit Sapi Ashif successfully obtained an NIB and increased the owner’s awareness of PIRT food safety standards and halal certification procedures. The impact of this activity includes meeting administrative legality and improving knowledge, confidence, and professionalism in business management. Intensive mentoring proved crucial in transforming informal businesses into formal, legally protected entities.